2021
DOI: 10.3390/agriculture11090866
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Arbuscular Mycorrhizal Fungal Communities between Farmland and Woodland in the Black Soil Region of Northeast China

Abstract: The black soil region of northeast China is a critical production base for commercial grain in China. Arbuscular mycorrhizal fungi (AMF) are widely present in terrestrial ecosystems and play a vital role in ecosystem stability. Here, we investigated the diversity and composition of AMF communities in farmland and woodland from 20 sites in the black soil region of northeast China using Illumina MiSeq sequencing. The sequences were classified into 1 phylum, 1 class, 4 orders, 8 families, and 11 genera. Glomerale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…Taking into account that the Shannon-Weaver index uses the richness and abundance of individuals per species, the diversity was certainly influenced by the greater abundance of AMF species in the areas of early secondary forest. The same was observed in other studies, where areas under environmental stress showed greater AMF diversity (Pereira et al 2014;Yang et al 2021). reported that in tropical dry forest with different successional stages, the area in initial regeneration showed higher production of propagules, which also reflected in greater diversity of AMF species.…”
Section: Discussionsupporting
confidence: 85%
“…Taking into account that the Shannon-Weaver index uses the richness and abundance of individuals per species, the diversity was certainly influenced by the greater abundance of AMF species in the areas of early secondary forest. The same was observed in other studies, where areas under environmental stress showed greater AMF diversity (Pereira et al 2014;Yang et al 2021). reported that in tropical dry forest with different successional stages, the area in initial regeneration showed higher production of propagules, which also reflected in greater diversity of AMF species.…”
Section: Discussionsupporting
confidence: 85%
“…The farmland management measures are similar, and chemical fertilizer is the main fertilizer. In recent years, the ratio of nitrogen, phosphorus, and potassium fertilizer has tended to be reasonable, and crop yields have tended to increase [38]. The study area has an obvious monsoon continental climate, with cold winters and hot summers, and dry winters and wet summers.…”
Section: Study Areamentioning
confidence: 99%
“…Moreover, the abundance and richness of indigenous AMF communities often correlates with soil physical properties such as soil organic matter (SOM), nitrogen, and precipitation [ 89 , 111 , 112 , 113 , 114 ], that can serve as clues for soil mycorrhizal potential. Such parameters can be modelled to predict inoculation success and post-inoculation effects on local microbiota.…”
Section: Future Directionsmentioning
confidence: 99%